Hemichorea-hemiballismus as a rare presentation of non-ketotic hyperglycemia: a case report - Kumar, Vijay; Patel, Kotha Vamshi Krishna; Raj, Rishav; Bhushan, Divendu; Hegde, Aniketh V. (International Journal of Basic & Clinical Pharmacology, 2022)
Hemichorea-hemiballismus is a hyperkinetic movement disorder on one side of the body resulting from involvement of the contralateral basal ganglia and striatum mainly. A 50-year-old female presented with a 5-days history of choreiform movements affecting the left upper and lower limb along with hemiface. Her plasma glucose was 576 mgl/dl and her urinary ketones were negative suggesting non-ketotic hyperglycemia. Computed tomography revealed hyper-density in right caudate and putamen consistent with diabetic striatopathy. Non-ketotic hyperglycemia is a rare cause of hemichorea-hemiballismus syndrome. Hemichorea-hemiballismus can be an unusual and rare presentation of diabetic elderly population especially females. Early diagnosis and treatment of hyperglycemia yields an excellent prognosis.